2021
DOI: 10.1101/2021.08.15.456437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structures of Tweety Homolog Proteins TTYH2 and TTYH3 reveal a Ca2+-dependent switch from intra- to inter-membrane dimerization

Abstract: Tweety homologs (TTYHs) comprise a conserved family of transmembrane proteins found in eukaryotes with three members (TTYH1-3) in vertebrates. They are widely expressed in mammals including at high levels in the nervous system and have been implicated in cancers and other diseases including epilepsy, chronic pain, and viral infections. TTYHs have been reported to form Ca2+- and cell volume-regulated anion channels structurally distinct from any characterized protein family with potential roles in cell adhesion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Specifically, focusing on mTTYH3, we introduced a T4 lysozyme (T4L) sequence between ECD1 (positions 107-209) and ECD2 (positions 260-386) to increase protein stability and solubility 32 . Due to the presence of disulfide bridges and glycosyl moieties 14,15,33 , we expressed this FLAG-tagged construct as a secreted protein in insect cells. Indeed, western blot analysis of the cell lysate revealed a complex migration pattern consistent with different stages in the protein biogenesis pathway.…”
Section: Isolated Mttyh3 Ecds Form Tetramers In Solutionmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, focusing on mTTYH3, we introduced a T4 lysozyme (T4L) sequence between ECD1 (positions 107-209) and ECD2 (positions 260-386) to increase protein stability and solubility 32 . Due to the presence of disulfide bridges and glycosyl moieties 14,15,33 , we expressed this FLAG-tagged construct as a secreted protein in insect cells. Indeed, western blot analysis of the cell lysate revealed a complex migration pattern consistent with different stages in the protein biogenesis pathway.…”
Section: Isolated Mttyh3 Ecds Form Tetramers In Solutionmentioning
confidence: 99%
“…The structures revealed a novel subunit topology common to all TTYH members, consisting of five transmembrane helices and a large a-helical extracellular domain (ECD). However, while the hTTYH paralogs and mTTYH3 were shown to exhibit a side-by-side dimeric organization involving interaction interfaces within the ECD and transmembrane regions, such an organization was shared by mTTYH2 only in the presence of calcium 14,15 . Conversely, it was suggested that in the absence of calcium, the dimers form by a head-to-head interaction between the ECDs of subunits from juxtaposing membranes 14 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations